PENGARUH BEBAN PAJAK TANGGUHAN, PROFITABILITAS, DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014) - Budi Setyawan (Universitas Pamulang, 2016)
This study aimed to analyze the relationship between deferred tax expense, profitability and tax planning to earnings management with leverage as control variables. Measuring earnings management are used in this study determined based approach to conditional revenue model (Stubben, 2010).The study population was manufacturing sub-sectors of automotive and components listed in the Indonesia Stock Exchange in 2010-2014, namely 12 companies using purposive sampling technique. Methods of data analysis using descriptive statistical analysis, test classic assumptions and hypothesis testing.These results indicate that the deferred tax expense, profitability and tax planning have a significant effect simultaneously on earnings management. The test results only partially profitability has a significant effect on earnings management. However, the deferred tax expense and tax planning does not have a significant effect on earnings management.